SKENARIO SUPPLY DAN DEMAND DALAM PENYEDIAAN AIR MINUM KOTA SEMARANG PADA PENCAPAIAN MDGS TAHUN 2015 HINGGA 2030 - Rezagama, Arya; S, Arwin (Jurnal Geografi, 2015)
One of the MDGs is to increase peoples access to clean water. Population growth and lifestyle needs ofwater cause Semarang rate increased rapidly while the coverage of drinking water Semarang limited (59%).By 2015 the MDG target 75% of the needs of the average supply of water about 3,442 l / s, and in 2030 ittakes 4,727 l / s at the 100% level of service. Condition of existing water sources either from the RiverGarang, ABT, baboons river continuity and quality of the constrained problem. Klambu- Kudu Channel havea channel-leakage problems is high that the discharge was not obtained in accordance with the initial designplanning. Supply conditions groundwater becoming increasingly declining so it needs a replacement sourceof water supply. Scenario SPAM Semarang to meet increasing Water Supply, described in Short-Term policy(75%) according to the MDGs in 2015, 2020 Medium Term (85%) and Long Term Semarang in 2030(100%). Development of water supply are key to SPAM derived from West Semarang Reservoir operatedJatibarang 2015 Phase I (Q = 500 LPS) and phase II in 2020 (Q = 1000Lps). In addition, there is apotential supply of river Blorong supply of 200 l / s and scout the river of 300 l / sec.